Cryptology : Classical and Modern with Maplets - Sigmon, Richard Klima. Neil (Discrete mathematics and its applications., 2012)
Introduction to CryptologyBasic Terminology Cryptology in Practice Why Study Cryptology?Substitution Ciphers Keyword Substitution Ciphers A Maplet for Substitution Ciphers Cryptanalysis of Substitution Ciphers A Maplet for Cryptanalysis of Substitution CiphersPlayfair Ciphers A Maplet for Playfair Ciphers Transposition Ciphers Columnar Transposition Ciphers A Maplet for Transposition Ciphers Cryptanalysis of Transposition CiphersMaplets for Cryptanalysis of Transposition CiphersADFGX and ADFGVX Ciphers A Maplet for ADFGX and ADFGVX CiphersThe Enigma Machine and Navajo CodeThe Enigma Cipher Mac.